Aplasia of the breast--reconstruction using a free tram flap - Tvrdek, M; Kletenský, J; Svoboda, S (Acta chirurgiae plasticae, 2001)
Breast aplasia and hypoplasia are found most frequently in Poland's syndrome but may also be the consequence of damage to the germ of the mammary gland in childhood. The authors present two cases of breast aplasia in which reconstruction was implemented by free transfer of a TRAM flap. The internal mammary vessels were used as recipient vessels, the condition of which was tested before surgery by Doppler. In both instances the reconstruction was implemented at the age of 19 years, and subsequently the areolomammillary complex was created and the contralateral breast corrected to achieve symmetry. The use of autologous tissue in the form of a free TRAM flap provides, in this indication, very good results that are permanent, and the problems associated with the use of implants are eliminated.
Keywords: Postoperative Complications; Child, Preschool; chirurgické laloky; nehodgkinský lymfom; Adult; dospělí; pooperační komplikace; Mammaplasty; Poland Syndrome; Polandův syndrom; předškolní dítě; Breast; Surgical Flaps; lidé; ženské pohlaví; Humans; prsy; Female; Lymphoma, Non-Hodgkin; mamoplastika